ANALYSIS OF ACCOUNTING INFORMATION SYSTEM DISTRIBUTION OF BOP RA FUND (CASE STUDY ON RA PERWANIDA KARANGREJO 02) - Nur Ika Mauliyah; Dwinda Agus Prastiwi (AKUNTABILITAS: Jurnal Ilmiah Ilmu-Ilmu Ekonomi, 2019)
The purpose of this study is to analyze the accounting information system of BOP RA funds distribution, the existence of accounting information system in the distribution of funds BOP RA as accounting information system has been run effectively as a provider of information. Analyzing the accounting information system conducted on the distribution of BOP RA funds. This research uses descriptive qualitative method that describes thoroughly to the implementation of accounting information system applied at school RA X and compared with technical guidance as well as theories related to accounting information system, so that it can produce result desired by researcher. The results of this study indicate that the accounting information system channeling BOP RA funds are in conformity with the reference and rules but not yet the formation of flowchart.